Analisis Kesadaran Siswa Kelas IV SDN Da’iring 1 terhadap Lingkungan melalui Pengelolaan Sampah; Materi IPAS - Sintawati, Siska; Lestari, Silviya Ayu; Na'miyah, Husniatun; Ruwaida, Mediana; Arifin, Haykal Bestanun; Rahmawati, Ika Dian (ARZUSIN, 2025)
This study is motivated by the low level of student awareness regarding the importance of environmental care, particularly in waste management, despite its direct impact on daily life within the school environment. The aim of this research is to analyze the environmental awareness of fourth-grade students at SDN Da’iring 1 through waste management activities in the IPAS subject “Our Environment is Under Threat.” A qualitative approach was used with interactive data analysis techniques, involving all 17 fourth-grade students as research subjects. Data were collected through observation sheets and multiple-choice tests to measure students’ knowledge and attitudes toward environmental issues. The results indicate that students demonstrate a generally good level of environmental awareness and concern, but most are still unable to manage waste effectively. These findings support the theory that knowledge and understanding of environmental issues are essential prerequisites for developing environmental concern, but do not necessarily lead to effective waste management behavior. The main conclusion of this study is that environmental awareness supported by cognitive understanding alone is insufficient to produce concrete action in waste management. The implications include theoretical contributions to the literature on environmental education in elementary schools and practical recommendations for schools to integrate clean classroom activities and recycling programs into thematic learning. This study also opens opportunities for further research on educational interventions aimed at improving students' waste management skills in elementary education.